ATYPICAL CLINICAL COURSE OF THE ACUTE MYOCARDIAL INFARCTION: CLINICAL AND ANAMNESTIC CHARACTERISTIC OF PATIENTS, MANAGEMENT AND OUTCOMES (DATA FROM REGISTRY OF ACUTE MYOCARDIAL INFARCTION) - A. А. Garganeeva; E. A. Kuzheleva; К. N. Borel; E. A. Parshin (Кардиоваскулярная терапия и профилактика)
Aim. To study  clinical and  anamnestic   specifics,  management and outcomes  of acute  myocardial infarction (MI) in patients  with atypical clinical presentation.Material and methods. Among the Tomsk population, those  having had acute MI in 2009-2014 y. were included, registered  in the database “Registry of Acute MI” (n=5602), and selected  to groups with atypical (n=1319) and common (n=4283) clinical presentation  of the MI onset. Statistics was done with software “Statistica 10”.Results. Atypical presentation  of MI took place in 23,5% cases. These patients were much older than those with common angina at MI onset; they had more prevalent arterial hypertension,  obesity, diabetes.  Also, the prevalence of anamnestic MI did not differ between groups, however autopsy revealed more common painless MI. Atypical  MI presentation patients sought for medical care in 28 days before the event of MI more frequently than those with typical clinical picture: 36% vs. 26% (p<0,001), but electrocardiography  was ordered only for a half of them (54%), that led to misdiagnostics of pre-infarction condition. Every second  patient with atypical MI was hospitalized to non-specialized  unit, where could not  receive  high-technology  treatment,   which hence  led  to  worse outcomes and prognosis.Conclusion. It is necessary to be careful with non-typical MI development possibility in  older  patients   with several  comorbidities,  and  with anamnesis of painless acute MI. Chance of fatal outcome in atypical MI is  10  times  higher  in this  group  than  in those  with typical clinical presentation.